Motor Competence as a Predictor of Breaststroke Swimming Learning Outcomes in Physical Education Programs - Siregar, Aidilla Pratiwi; Raufi, Afwa (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study investigated whether motor competence serves as a significant predictor of breaststroke swimming learning outcomes among undergraduate students enrolled in a physical education program at a higher education institution in Indonesia. The study further examined which specific components of motor competence most substantially contribute to swimming performance acquisition. Materials and methods: A quantitative predictive correlational design was employed involving 84 undergraduate students (52 males, 32 females; mean age = 20.4 ± 1.2 years) from Sekolah Tinggi Olahraga dan Kesehatan (STOK) Bina Guna, Medan, Indonesia. Motor competence was assessed using the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2), encompassing coordination, balance, agility, and bilateral integration domains. Breaststroke swimming performance was evaluated through a validated observational rubric incorporating stroke mechanics, kick execution, breathing coordination, and temporal efficiency over 50 meters. Data were analyzed using Pearson product-moment correlation and hierarchical multiple regression, with assumptions verified through normality, linearity, and homoscedasticity diagnostics. Results: Motor competence demonstrated a statistically significant positive correlation with breaststroke learning outcomes (r = .62, p < .001). Hierarchical multiple regression revealed that the composite motor competence score accounted for 38.0% of the variance in breaststroke swimming performance (R² = .380, adjusted R² = .372; F(1,82) = 50.21, p < .001). When disaggregated, coordination (β = .41, p < .001) and balance (β = .29, p = .003) emerged as the most influential predictors, collectively explaining 34.7% of the variance. Agility contributed modestly (β = .14, p = .042), while bilateral integration did not reach statistical significance (β = .08, p = .216). Conclusions: Motor competence constitutes a meaningful predictor of breaststroke swimming learning outcomes in higher education physical education settings. Coordination and balance represent the primary motor competence domains influencing swimming skill acquisition. These findings underscore the pedagogical value of integrating systematic motor competence screening and targeted preparatory motor skill interventions prior to formal swimming instruction to optimize learning trajectories.